Calculation of modes of coating of composite coverings on bearings of sliding - J.V. RYADCHENKO; G.V. RYADCHENKO (Advanced Engineering Research, 2008)
In work results of theoretical calculation of basic elements of the closed technological package for coating composite coverings are brought.